(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2024)
This study serves as a significant reference for practitioners and researchers to explore further the disparities in the actual practices of external conventional and Shariah reviewers. It is important as the current guidelines do not elaborate in detail on the practices to give more space for the company to manage their own situation on the ground. The research adopted a qualitative research method and conducted interviews with four external review officers, comprising both conventional and Shariah reviewers. The study reveals that both types of reviewers share similar attributes of the reviewer. However, in terms of the review process, only follow-up issues exhibit similarity, while risk assessment and output of the review. It is essential to acknowledge that the findings of this study are solely based on the results obtained from the conducted interviews and may not fully represent the practices of all external review officers in Malaysia. To gain a more comprehensive understanding of the variations in practices among different reviewers, further research in this area is encouraged. Such future research could investigate deeper into the review process, encompassing planning, execution, and reporting, to draw more robust conclusions about the real practices of external conventional and Shariah reviewers.